2005
DOI: 10.1177/0885066604273481
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine in the Treatment of Withdrawal Syndromes in Cardiothoracic Surgery Patients

Abstract: Dexmedetomidine (Precedex, Abbott Laboratories, Abbott Park, IL) is an alpha 2 adrenergic agonist that possesses a high ratio of specificity for the alpha 2 versus the alpha 1 receptor. It is currently approved for the provision of sedation during mechanical ventilation in adults. Given previous experience with clonidine for the treatment of substance withdrawal and the preliminary anecdotal experience with dexmedetomidine, it appears that dexmedetomidine may be a useful agent for treatment of substance withdr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 26 publications
1
47
0
2
Order By: Relevance
“…Second, because we studied healthy cocaine-naïve subjects, the results cannot be extrapolated to chronic cocaine abusers. However, in isolated case reports dexmedetomidine has been effective in reducing agitation, tachycardia, and hypertension in poly-substance abusers undergoing withdrawal from cocaine, alcohol, and opiates (26,27). Third, here we focused on the human cutaneous circulation and skin sympathetic activity.…”
Section: Effectiveness and Safety Of Dexmedetomidine As A Countermeasmentioning
confidence: 99%
“…Second, because we studied healthy cocaine-naïve subjects, the results cannot be extrapolated to chronic cocaine abusers. However, in isolated case reports dexmedetomidine has been effective in reducing agitation, tachycardia, and hypertension in poly-substance abusers undergoing withdrawal from cocaine, alcohol, and opiates (26,27). Third, here we focused on the human cutaneous circulation and skin sympathetic activity.…”
Section: Effectiveness and Safety Of Dexmedetomidine As A Countermeasmentioning
confidence: 99%
“…For example, delirium is a known adverse effect of β-blocker therapy; and one study showed an increase in delirium in AWS when propranolol was used in treatment [104,105]. Two medications in this class have shown some promise, but only as adjuncts: clonidine and dexmedetomidine [64,[106][107][108][109][110][111][112][113][114][115]. However, studies on these 2 medications, especially on the recently popular medication dexmedetomidine, have been small and limited to case reports or small case series; but there may be some promise for use of dexmedetomidine if used as an adjunct to standard therapy with benzodiazepines, phenobarbital, or propofol.…”
Section: Other Nonsedative Medicationsmentioning
confidence: 99%
“…Nevertheless, a few retrospective case reports and series support its potential use 65,66 , ameliorating the hemodynamic effects during withdrawal from illicit drugs and long-term sedation in the ICU. The two largest series are by Tobias 65 (7 patients) and Baddigam et al 66 (3 patients). The infusion dose was in the range 0.25-0.7 µg.kg -1 .h -1 and the duration of treatment was ≤ 3 days.…”
Section: Treatment Of Withdrawalmentioning
confidence: 99%